Differentiability of convex envelopes - Kirchheim, B; Kristensen, J (2001)
We prove that the convex envelope of a differentiable, or C1,α-function f is C1, or C1,α respectively, provided only that the function satisfies the very mild growth condition that f(x) tends to +∞ if |x| does so. © 2001 Académie des sciences/Éditions scientifiques et médicales Elsevier SAS.